Monetary Policy Transmission and Trade-offs in the United States: Old and New - Boris Hofmann; Gert Peersman (Center for Economic Studies and ifo Institute (CESifo), 2017)
This study shows that, in the United States, the effects of monetary policy on credit and housing markets have become considerably stronger relative to the impact on GDP since the mid-1980s, while the effects on inflation have become weaker. Macroeconomic stabilization through monetary policy may therefore have become associated with greater fluctuations in credit and housing markets, whereas stabilizing credit and house prices may have become less costly in terms of macroeconomic volatility. These changes in the aggregate impact of monetary policy can be explained by several important changes in the monetary transmission mechanism and in the composition of macroeconomic and credit aggregates. In particular, the stronger impact of monetary policy on credit is driven by a much higher responsiveness of mortgage credit and a larger share of mortgages in total credit since the 1980s.
Keywords: E52; 330; monetary policy trade-offs; monetary transmission mechanism; inflation; credit; house prices